2020
DOI: 10.1038/s41598-020-76335-4
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide analog [18F]F-HPA-12 detects sphingolipid disbalance in the brain of Alzheimer’s disease transgenic mice by functioning as a metabolic probe

Abstract: The metabolism of ceramides is deregulated in the brain of Alzheimer’s disease (AD) patients and is associated with apolipoprotein (APO) APOE4 and amyloid-β pathology. However, how the ceramide metabolism changes over time in AD, in vivo, remains unknown. Distribution and metabolism of [18F]F-HPA-12, a radio-fluorinated version of the ceramide analog N-(3-hydroxy-1-hydroxymethyl-3-phenylpropyl) dodecanamide, was investigated in the brain of AD transgenic mouse models (FAD) on an APOE4 or APOE3 genetic backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Finally, our analysis comprised a selected number of sphingolipids, e.g., S1P and seven ceramides. Though the analysis of additional sphingolipids, such as hexosylceramides and sulfatides, is undoubtedly interesting in association to FAD mutation and age ( Crivelli et al, 2020b ), we here focused on S1P and ceramide as they are important signaling sphingolipids and commercial MS standards were available for these lipids. Brain sphingosine levels were below the detection limit of our LC-MSMS setup and were therefore not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our analysis comprised a selected number of sphingolipids, e.g., S1P and seven ceramides. Though the analysis of additional sphingolipids, such as hexosylceramides and sulfatides, is undoubtedly interesting in association to FAD mutation and age ( Crivelli et al, 2020b ), we here focused on S1P and ceramide as they are important signaling sphingolipids and commercial MS standards were available for these lipids. Brain sphingosine levels were below the detection limit of our LC-MSMS setup and were therefore not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our LC-MS/MS analysis also indicated that (1R,3S)-HPA-12, which has been widely used as a CERT inhibitor [16,[34][35][36], is converted to its phosphocholine-conjugated metabolite presumably via the cidSM-synthesis pathway and also by host SMSes (Figure 7D). Based on these data, we here suggested that (1R,3S)-HPA-12 exerts its anti-chlamydia activity not only as an inhibitor of CERT or cidSM-synthesis but also via putative toxic effects of its phosphocholine adduct.…”
Section: Discussionmentioning
confidence: 64%
“…In this sense, some lipids showed statistically significant different levels between AD and non-AD groups. Specifically, an increase in gangliosides 22 , 23 , sphingomyelins (SM) 24 , 25 , lysophospholipids (LPL) 26 , 27 and monounsaturated fatty acids 28 , 29 and a decrease in sulfatides 23 , 24 were observed in AD mice compared to WT. However, these studies showed a wide variety of experimental conditions.…”
Section: Introductionmentioning
confidence: 99%